Bimbingan Kelompok Teknik Contextual Teaching and Learning (CTL) Efektif Meningkatkan Kepercayaan Diri Peserta Didik - Syapitri, Novia; ., Romiaty; Pan Pangestie, Esty (JURNAL PENDIDIKAN, 2023)
The purpose of this study was to determine the effectiveness of group counseling using the Contextual Teaching and Learning (CTL) technique in increasing the self-confidence of students in class VIII-7 at SMP Negeri 2 Palangka Raya. The 'One Group Pre-Test and Post-Test Design' is the pre-experimental research design used in this study. Six children from class VIII–7 at SMPN 2 Palangka Raya were chosen as samples for this study, and samples were collected using the Purposive Sampling Technique to ensure that they met the sample selection criteria. A questionnaire is the primary to collect data. Then, using parametric statistics from the Paired Sample T-test (SPSS Program Version 25), the data were examined. The results revealed that the calculated t value compared to the t table value is 39.385 > 2.571 and the calculated t value compared to the paired sample t test was sig. 0.000 0.05. This is also supported by the calculation of R square to determine the percentage of research effectiveness, using this Summary Model, which came out to be 0.422 or 42%. Therefore, the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected, indicating that group counseling services contextual teaching and learning (CTL) methodologies are effective to increase students' self-confidence at SMP Negeri 2 Palangka Raya.